Effectiveness of Problem-Based Learning and Discovery Learning Models on Learning Outcomes of Social Science Students - Walipah, Walipah; Firdaus, Riril Mardiana; Chasanah, Farida (Tarbiyah : Jurnal Ilmiah Kependidikan, 2024)
Research will be conducted to determine the description of the problem-based learning and discovery learning models to improve student learning outcomes, the differences in cognitive and affective learning outcomes between experimental and control classes, and the effectiveness of the problem-based learning and discovery learning models in improving student learning outcomes—quantitative research with an experimental nonequivalent control group design. The population is class VII students of SMP (Junior High School) Negeri 1 Bululawang 2023/2024, totaling 52 students. The sampling technique uses saturated sampling. Data collection uses test and observation techniques. Data analysis techniques use the t-test and Manova test. The research results showed that the effectiveness of the experimental class compared to the control class was 0.032, thus stating that Ha was accepted. The implications of this research show that learning Social Sciences, which has been considered rote, can become applied science using the Problem-Based Learning model.